THE ROLE OF ESG, ASSET STRUCTURE AND CAPITAL STRUCTURE IN SUSTAINING COMPANY PERFORMANCE - Handayani, Puspita; Cahyani, Nabila Duwi; Pratiwi, Adhitya Putri (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
This research aims to examine the relationship between Environmental, Social, and Governance (ESG), Asset Structure, and Capital Structure on Company Performance in firms that disclose ESG and are listed on the Indonesia Stock Exchange from 2019 to 2023. A purposive sampling method was applied in this quantitative study, utilizing secondary data from companies' annual financial reports. The sample consists of 8 companies observed over five years, resulting in 40 total observations. The analysis was conducted using panel data regression with the assistance of Eviews 12 software. The findings reveal that ESG has no significant impact on Company Performance. However, Asset Structure positively influences Company Performance, whereas Capital Structure does not show any significant effect.